2011
DOI: 10.1166/jnn.2011.4720
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of the Young's Modulus of a Single Halloysite Nanotube Using a Transmission Electron Microscope with a Bending Stage

Abstract: Halloysite nanotubes (HNTs) are a naturally occurring nanotubular aluminosilicate mineral, which has been used to prepare nanocomposites with exceptional mechanical properties. In order to understand the roles of nanotubes during the deformation and fracture of nanocomposites, a state-of-the-art transmission electron microscope (TEM) with a bending stage was used to measure the Young's modulus of individual HNTs. TEM micrographs showed that the HNTs were surprising flexible and could be bent to almost 90 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…When the external diameter of Hal ranged between 50 and 160 nm, the average elastic modulus was 140 GPa. This result is in agreement with the observation made by Lu et al (2010). When the external diameter of Hal was less than 50 nm, the elastic modulus suddenly increased to 460 GPa.…”
Section: Mechanical Properties Of Hal Nanotubesupporting
confidence: 93%
See 2 more Smart Citations
“…When the external diameter of Hal ranged between 50 and 160 nm, the average elastic modulus was 140 GPa. This result is in agreement with the observation made by Lu et al (2010). When the external diameter of Hal was less than 50 nm, the elastic modulus suddenly increased to 460 GPa.…”
Section: Mechanical Properties Of Hal Nanotubesupporting
confidence: 93%
“…Abdullayev et al (2012) estimated that the Hal bending stiffness and tensile strength were reduced due to the decrease in wall thickness resulting from the acid treatment. However, a more accurate evaluation of the effects of the acid treatment on the change in the mechanical properties of Hal could be achieved only by directly measuring the Young's modulus of Hal using proposed methods based on TEM (Lu et al, 2010) and atomic force microscopy (AFM) (Lecouvet et al, 2013a). The aforementioned studies revealed the stability of Hal in acid or alkaline solutions, which is meaningful for the understanding of the behavior of Hal in natural environments, e.g., how its surface reactivity is possibly modified in acidic soils.…”
Section: Structural and Morphological Changes Under Acid Or Alkaline mentioning
confidence: 99%
See 1 more Smart Citation
“…At first glance, it might seem like a negative effect. Nevertheless, based 4,0x10 5 6,0x10 5 8,0x10 5 1,0x10 6 1,2x10 6 Intensity …”
Section: Results and Disscusionmentioning
confidence: 99%
“…The empirical formula is Al2(OH)4Si2O5(2H2O). HNT do not reach such high modulus of elasticity as CNT (up to 1TPa) [1], but still reach a very high values around 130 GPa [6]. Another advantage is that HNT have a better dispersion in large number of polymer systems in comparison with a commercially used organoclays.…”
Section: Introductionmentioning
confidence: 99%